Sustaining constructive learning environment: the role of multi-sources regulation - Abd Rahman, Fadzilah; Scaife, Jon (Elsevier, 2012)
Sustaining constructive learning environment is a multi-sources need progression. It occurs better when the diverse sources that are necessary are present and operating simultaneously. How learners differ in using their learning environment and how these differences may beneficial to learners? This paper discuss the data emerges from the questionnaire and semi-structured interview that illustrates reflections concerning to what extent multi-sources have contributed in developing learners teaching knowledge. A finding shows that different types of sources are necessary in the learning process. In addition, the finding indicates that knowledge developed via experiential activities is of the greatest importance for the learners.